2008
DOI: 10.1029/2008gl033968
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the mixing state, mass, and optical size of individual black carbon particles in urban and biomass burning emissions

Abstract: [1] In situ measurements of the mass, mixing state, and optical size of individual black-carbon (BC) particles in the fine mode (90 -600 nm) have been made in fresh emissions from urban and biomass burning sources with an airborne single-particle soot photometer. Contrasts between the two sources are significant and consistent. Urban BC tends to smaller sizes, fewer coated particles, thinner coatings, and less absorption per unit mass than biomass-burning BC. This suggests that urban BC may have a longer lifet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
442
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 447 publications
(488 citation statements)
references
References 18 publications
43
442
3
Order By: Relevance
“…As discussed in relation to the observed PM and OC emission flux estimates (Figure 9, right), strong signatures of biogenic burning were observed on 21 and 25 September 2006. Isolated biomass burning signatures from the WP-3 aircraft have been reported on two other days as well [Schwarz et al, 2008]. While the already high model PM 2.5 biases within the aircraft comparisons argues against an additional burning source, it is nonetheless possible that the nine flight days within the aircraft analysis undersampled biomass burning conditions during the 49-day period of the surface analysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As discussed in relation to the observed PM and OC emission flux estimates (Figure 9, right), strong signatures of biogenic burning were observed on 21 and 25 September 2006. Isolated biomass burning signatures from the WP-3 aircraft have been reported on two other days as well [Schwarz et al, 2008]. While the already high model PM 2.5 biases within the aircraft comparisons argues against an additional burning source, it is nonetheless possible that the nine flight days within the aircraft analysis undersampled biomass burning conditions during the 49-day period of the surface analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Ethylene is measured at 10-s resolution with the photoacoustic laser spectroscopy technique described by Kuster et al [2005]. Elemental carbon is determined by single particle soot photometer measurements [Schwarz et al, 2006[Schwarz et al, , 2008. Size (and volume) distribution measurements of aerosol were made aboard the NOAA P-3 at 1-s time resolution by laser optical particle counters, similar to the measurements made during the ICARTT/NEAQS-2004 field project [Brock et al, 2008].…”
Section: Observations and Details Of Analysismentioning
confidence: 99%
“…C * abs (λ) gradually decreased from about 5.7 ± 0.3 m 2 g -1 at D BC = 100-150 nm to 4.4 ± 0.2 m 2 g -1 at 300 nm. The major mass fraction of BC in urban plumes in Japan and the United States was in the range of 100 to 500 nm peaking at around 180 nm (Kondo et al 2006;Schwarz et al 2008). In addition, measurements of the size distributions were made by a SP2 (Shiraiwa et al 2008) at Fukue Island (32.8 • N, 128.7…”
Section: Calculated Mass Absorption Cross Sectionmentioning
confidence: 99%
“…In contrast, the EC core size should be bigger than 120 nm and the D shell /D core ratio should be larger than 3.0 in other seasons. These results did not match with EC core sizes from biomass burning and urban emissions (Schwarz et al 2008). It was found that the MAE of EC was higher when it internally mixed with both OM and sulfate than only coating with OM in the Pearl River Delta region (Yu et al 2010).…”
Section: Impact Of Chemical Compositions On Mae Of Ecmentioning
confidence: 52%
“…As more OM were emitted from biomass burning, it suggested that EC particles were coated with more OM in autumn, winter and spring. Furthermore, the volume-equivalent diameter of EC core derived from biomass burning (number median geometric diameter = 140 nm) was found to be higher than that from urban emission (number median geometric diameter = 70 nm) (Schwarz et al 2008), and the EC core size thus have bigger size during autumn, winter and spring. According to Fig.…”
Section: Impact Of Chemical Compositions On Mae Of Ecmentioning
confidence: 99%